Teaching Software Evolution in Open Source. - Petrenko, Maksym; Poshyvanyk, Denys; Rajlich, Václav; Buchta, Joseph (Computer (00189162), 2007)
The article discusses the use of open source software for teaching software engineering. Real-world software development often involves the modification of large, existing systems, whereas classroom projects tend to be much smaller and built from the ground up. Open source software as an educational tool can help bridge the gap. The authors describe their experience teaching an advanced software engineering course at Wayne State University, wherein they had students develop skills in software evolution by adding functionality to an extant system..